Practical breast pathology : a diagnostic approach - Atkins, Kristen A.; Kong, Christina S. (Pattern recognition series, 2013)
Apply a systematic pattern recognition method to achieve more accurate diagnoses with Practical Breast Pathology: A Diagnostic Approach. Using a practical, pattern-based organization, this volume in the Pattern Recognition series guides you efficiently and confidently through the evaluation of even the most challenging neoplastic and non-neoplastic specimens in breast pathology, and also highlights patterns crucial to radiologic diagnosis.